Analisis Resiko Transformasi Mobil Berbahan Minyak ke Mobil Listrik Dengan Decision Tree - Abdul Halim Anshor; Sugeng Budi Rahardjo (Bulletin of Information Technology (BIT), 2023)
The development of the world of transportation has increased rapidly, this is marked by the emergence of electric cars. The changes experienced by society are so fast to switch from fuel cars to electric cars. Electric cars have various advantages of being environmentally friendly, not producing pollutant gas emissions, being faster, cost-effective and more comfortable. In addition to the advantages provided there are also several risks from the transformation of oil-fueled (bbm) cars into electric cars including expensive car prices, charging infrastructure, shorter mileage, electric car batteries have a limited lifespan. This study aims to analyze the risk mitigation of transforming oil-fueled cars into electric cars. In this case study, the researcher uses two kinds of attributes, namely the price of the car and the emissions it produces. The method used is to calculate each gain information from the attribute used by looking at the highest gain value, it will be known how big the risk is for the transformation of oil-fueled cars (bbm) to electric cars. and what factors (attributes) most determine the risk. . It is hoped that this research can help electric car developers and entrepreneurs to continue to improve the performance of existing electric cars.